Neposluš(a)nost radia - Bizilj, Ljerka (Javnost (Ljubljana), 2008)
The article focuses on the turning points in the history of the Slovenian radio after 1945 that went beyond the radio as a medium and were related to the broader social conditions in the period of a single-party rule, and to the attempts of the Yugoslav authorities to create a single Yugoslav nation and hence to limit radio broadcasts in the Slovene language. The national radio had a crucial role in the breakthrough of national television in the late 1950s, and significantly changed the media landscape with a light, personalized programming introduced in 1972 by its new channel, Val 202. In the late 1980s, the Slovenian radio was in the frontlines of the struggle for political democratization and national emancipation, fighting for democracy and for Slovenia, and, like always, ignoring any attempts to be silenced.
Keywords: Jugoslavija; radio; Yugoslavia; Slovenia; Slovenija; 1945/1990; politične razmere; mass media; množični mediji; vloga; slovenščina; Slovene; nadzor; demokratizacija